Rhetoric vs. Reality What We Know and What We Need To Know About Vouchers and Charter Schools - Timpane, Michael (RAND Corporation, 2001)
How can the education of our nation's children be improved? Vouchers and charter schools aim to improve education by providing families with more choice in the schooling of their children and by decentralizing the provision of educational services. While supporters argue that school choice is essential to rescue children from failing schools, opponents claim that it may destroy America's public education system. The authors undertake an exhaustive and critical view of the evidence on vouchers and charter schools. The book is a useful, unbiased primer for all those interested in this controversial topic.